2021 Community Vitality Survey : Black in Quebec - Black Community Resource Centre (BCRC) (2021)
This report offers a comprehensive overview of the 2021 Community Vitality Survey which was conducted by the Black in Quebec project team. Black in Quebec was launched in Fall 2019 and was a research project by the Black Community Resource Centre (BCRC) which researched the well-being and vitality of Quebec's English-speaking Black Community (ESBC). This is the third report to be released by the project team and complements the two previous research based publications. The first published report was Quebec's English-speaking Black Community: An Analysis of Outcomes and Information Gaps which was based on an assessment of currently available information pertaining to the English-speaking Black Community in Quebec. The second report to be released was entitled Black in Quebec presents: In Focus and it presented an overview of the Focus Groups conducted by the project team from May to December of 2020. This report focuses exclusively on the 2021 Community Vitality Survey which was conducted from April to June 2021 and provides a detailed overview of the survey. It is the last research based report to be released by the Black in Quebec project before the release of a final, comprehensive project summary report.

Quebec's English-speaking Black Community : An Analysis of the Outcomes and Information Gaps - Black Community Resource Centre (BCRC) (2021)
Black in Quebec (BIQ) is a research project being undertaken by the Black Community Resource Center (BCRC), a non-profit organization founded in 1995, which serves Montreal’s English-speaking Black Community (ESBC) by providing individuals with services and information that they need. The BIQ project seeks to answer the Research Question: What is the relative well-being of the English-speaking Black community in Quebec? The relatively unique positioning of the ESBC in the Quebec landscape, being both a visible minority and linguistic minority group, necessitates that research be conducted to further understanding of the experiences and situations facing this community, which are particular to the group or shared more widely across society. The overall vision of this project is to consolidate the collection and dissemination of data that pertains to Quebec’s English-speaking Black community and share this information across a variety of institutions, including Black community organizations, public institutions, and social research groups.

Black in Quebec : Summary Report 2020-2021 - Black Community Resource Centre (BCRC) (2021)
In Quebec, there is a population of around 320,000 people who identify as members of the Black community. In Quebec's Black community, just under 60,000 (around 1 in 5 people) are categorized as members of the English-speaking community (Statistics Canada, 2016). The Black in Quebec Project commenced in Fall 2019 with the drafting of the project and in February 2020, the Project Researcher (John Davids) and Research Assistant (Xiaoyan Fang) were hired by the BCRC. The purpose of the project is to fill the gaps in the knowledge about the English-speaking Black Community (ESBC) in Quebec. In Quebec and Canada, there is a lack of disaggregated race-base data that measures critical variables describing the socio-economic and psycho-social status of the English-speaking Black Community. Thus, when it came to exploring the state and vitality of the ESBC, there were and continues to be deficiencies in the publicly available data and knowledge. Being a study about a population that is both a racialized and linguistic minority in Quebec, the Black in Quebec Project attempts to fill some of the gaps in the collection of data, its analysis and storage. It presents an improved understanding regarding the unique situation and challenges facing the ESBC in Quebec.

The Black Community Resource Centre Presents : The Infographic Series : Demographics of Quebec's English-speaking Black Population - Black Community Resource Centre (BCRC) (2022)

The Education to Employability Study - Black Community Resource Centre (BCRC); Provincial Employment Roundtable of Quebec (2022)
In Québec, both the Black community and the English-speaking community occupy relatively precarious economic and employment positions: both experience higher-thanaverage unemployment rates and earn lower median after-tax incomes compared to the province’s total population. The English-speaking Black Community (ESBC) sits at the intersection of these two communities, and experiences the double marginalization of being both a racial and linguistic minority in Québec.

L'étude éducation à l'emplois (E2E) - Black Community Resource Centre (BCRC); Provincial Employment Roundtable of Quebec (2022)
Au Québec, la communauté noire et la communauté d'expression anglaise occupent toutes deux des positions relativement précaires sur le plan économique et de l'emploi : toutes deux connaissent des taux de chômage supérieurs à la moyenne et gagnent des revenus médians après impôt inférieurs à ceux de la population totale de la province. La communauté noire d'expression anglaise (CNEA) se trouve à l'intersection de ces deux communautés et subit la double marginalisation d'être à la fois une minorité raciale et linguistique au Québec.